Threshold effects and ion-pair production in the dissociative recombination of HD+ - Lange, Michael; Levin, J.; Gwinner, G.; Hechtfischer, U.; Knoll, L.; Schwalm, Dirk; Wester, Roland; Wolf, Andreas; Urbain, X.; Zajfman, D. (Physical review letters, 1999)
Sharp thresholds are observed in the dissociative recombination cross section of vibrationally cold HD+ in the energy range where new channels H(1s)+D(n) [or D(1s)+H(n)] with n>2 open. The occurrence of these thresholds, not predicted by current theoretical calculations, contradicts the current assumption that the size of the total cross section can be calculated without accounting for the detailed branching ratios. An indirect signature of ion pair production is also found in the data, suggesting a significant branching into that channel.